Zoogeographical structure of Cerambycidae beetles family from the collection of KarSU Nature Museum - Abukenov, V.S.; Kachur , O.G. (Fundamental and Experimental Biology, 2015)
The article presents the results of the zoogeographic of Cerambycidae beetles family structure studies on the of the entomological collection of the University Nature Museum. Zoogeographical analysis involves the genesis of the fauna individual elements assessing and union types which are similar in time and place of their origin in faunal complexes (belonging to a particular type of fauna). When you select a geographic complexes you should take into consideration not only the general character of the area and zonal-landscape attachment of species, but also known data about the centers of the origin. This analysis has shown that the Holarctic genera makes up the core of the Kazakh uplands fauna at the generic level, and unique species of the indo-malayan genera makes the smallest part of the collection.